2021
DOI: 10.1590/1678-4324-2021210186
|View full text |Cite
|
Sign up to set email alerts
|

Methyl Eugenol, 1,8-Cineole and Nerolidol Rich Essential Oils with their Biological Activities from three Melaleuca Species Growing in Tarai Region of North India

Abstract: The essential oils from the fresh leaves of three Melalecua spp. viz; Melaleuca leucadendron (L.) Melaleuca linariifolia Sm. and Melaleuca bracteata F. Muell. growing in Tarai region of North India were analyzed by a combination of gas chromatography/mass spectrometry. The analysis revealed the presence of several constituents of industrial and pharmacological importance. M. leucadendron essential oil was found to be dominated by E-nerolidol (85.7%) rich chemotype. 1,8-cineole (61.1%) along with significant pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 49 publications
1
5
0
Order By: Relevance
“…The antifungal activity of HCCAO and HCCRO was significantly lower compared to standard fungicide Carbendazim (100%), even at a higher concentration (750 µL/mL) against both the tested fungi. Antifungal activity was also demonstrated for the essential oil at 50–500 µL/mL in a previous study [ 26 ].…”
Section: Resultssupporting
confidence: 53%
“…The antifungal activity of HCCAO and HCCRO was significantly lower compared to standard fungicide Carbendazim (100%), even at a higher concentration (750 µL/mL) against both the tested fungi. Antifungal activity was also demonstrated for the essential oil at 50–500 µL/mL in a previous study [ 26 ].…”
Section: Resultssupporting
confidence: 53%
“…Studies in the literature suggest that the use of antioxidant substances can prevent or reverse the occurrence of morphological changes in models of oxidative imbalance [30]. Considering that plant extracts rich in citral and limonene have previously been shown to have antioxidant potential [31], the results obtained in this work suggest a cytoprotective potential of Lippia alba based on its antioxidant effects. Oxidative stress leads to the ROS accumulation, which is responsible to modify the cellular architecture through oxidation of membrane phospholipids, dysfunction of structural proteins, enzymes, and nucleic acids.…”
Section: Discussionmentioning
confidence: 62%
“…In addition, excellent antioxidant and antimicrobial effects of isomenthone have been reported (Alizadeh et al, 2021). Joshi et al (2022) also reported significant antimicrobial properties of 1,8‐cineole against S. aureus , E. coli , and Salmonella typhymurium .…”
Section: Resultsmentioning
confidence: 96%